Respon pertumbuhan dan produksi ubijalar (Ipomoea batatas L.) terhadap pemberian beberapa jenis pupuk pada Inceptisol Amban - Olin Ulunggi; Ishak Musaad; Kati Syamsudin Kadang Tola; Saraswati Prabawardhani (Agrotek, 2020)
This study aims to determine the response of growth and yield of sweet potato (Ipomoea batatas L.) to the application of several types of fertilizers on Inceptisol soil in Amban. Fertilizer application with the following doses: P0 = No fertilizer (control), P1 = NPK fertilizer (standard dose) 300 kg/ha = 225 g/mound, P2 = KCl fertilizer, 50 kg/ha = 375 g/ mounds, P3 = Papua nutrient granular fertilizer 300 kg/ha = 225 g/mounds, P4 = Papuan nutrient liquid fertilizers 10 liters/ha = 7.5 ml/mounds. P1, P2 and P3 treatments were carried out at 2 week after plant (WAP), while the P4 treatment was carried out at the age of 2, 4 and 6 WAP. The results showed that the application of several types of fertilizers did not have a significant effect on tendril length, tuber weight, wet weight and dry weight of tendrils in all observations. The analysis results of the soil chemical properties found that the soil pH was 4.63 (acidic), C-organic was 0.89% (very low), N-soil was 0.14% (low), Pavailable was 4.17 ppm (very low), and base saturation was 32.92% (low). The soil CEC was 4.94 cmol(+)/kg with exchangeable cations of kalsium, magnesium, potassium and sodium were 1.19 cmol(+)/kg (low), 0.34 cmol(+)/kg (very low), 0.07 cmol(+)/kg (very low) and 0.03 cmol(+)/kg (very low), respectively. The highest tendril length produced by KCl fertilizer, but Papua Nutrient granule yielded the best of average fresh weight of tendril, average dry weight of tendril, and tuber weight of sweet potato.